Poszukiwanie korzeni i tradycji rodzinnych. Aspekt dydaktyczny i wychowawczy seminarium pedagogicznego - Szablicka-Żak, Jolanta (Karkonoska Państwowa Szkoła Wyższa, 2011)
This text is an attempt to share the experience and observations resulting from a one-year pedagogic seminar conducted for students attending extramural courses at the Institute of Pedagogy at the University of Wrocław, between 2005 and 2008. The theme of the family and its multidimensional depictions discussed as part of the seminar was subjected to an in-depth analysis within the framework of the historical and anthropological context. Didactic and educational purposes, as well as research methods were set forth. The seminar gave rise to dozens of dissertations on the family and the traditions it cultivates. The said studies embraced life stories of a few generations, starting from the late great-grandparents and grandparents to the contemporary family members, including the authors and their children, thus giving an interesting account of the twentieth century history and the changes in the family structure. Students pointed out that family bonds were both restored and tightened asa result of collecting materials and holding conversations. Furthermore, while gathering materials and drafting their dissertations, students became aware of the fact that each and every person contributes to shaping history and is responsible for what constitutes the present and the future of not only his/ her family or local community, but at times also the homeland.
Keywords: family; history; tradition